Estrés y su influencia en el desempeño laboral y académico - Quirola Ruiz, Walter Ruben (2021)
In the center of the Parroquia La Unión of the Province of Los Ríos, a 20-year-old young man, who is in the first semester of the CPA career at the Technical University of Babahoyo, was found to have emotional problems. This work has the research line of the University which is that of "education and Social development", supported by the research line of the Faculty: "human talent education and teaching", likewise is the research line of the career that is "prevention and diagnosis", all these lines are supported by the sub-line "effects on the development of educational activities, due to the disrespect of school students." The direct beneficiaries of this work were: their relatives, neighbors, friends, workplace and educational institution, because the patient, feeling well and will not be a burden for them, will be able to function alone and carry out any activity they want, independently, The objective of this work is to identify the influence that stress has on work and academic performance for psychological care and to improve symptoms, for which the respective psychological techniques were used such as: clinical interview, clinical observation and psychological tests allowed carry out a good clinical diagnosis, for its treatment holistic psychotherapeutic techniques were used since it worked with some cognitive behavioral therapy techniques and with the podomoro method, later on the way in which it was worked will be explained.